Reticulomics: Protein-Protein Interaction Studies with Two Plasmodesmata-Localized Reticulon Family Proteins Identify Binding Partners Enriched at Plasmodesmata, Endoplasmic Reticulum, and the Plasma Membrane. Issue 3 (9th September 2015) - Kriechbaumer, Verena; Botchway, Stanley W.; Slade, Susan E.; Knox, Kirsten; Frigerio, Lorenzo; Oparka, Karl; Hawes, Chris
Abstract : Protein interactions for two plasmodesmata-localized reticulon proteins suggest that these proteins, in addition to a role in endoplasmic reticulum modeling, may play important roles in linking the endoplasmic reticulum and plasma membrane. Abstract: The endoplasmic reticulum (ER ) is a ubiquitous organelle that plays roles in secretory protein production, folding, quality control, and lipid biosynthesis. The cortical ER in plants is pleomorphic and structured as a tubular network capable of morphing into flat cisternae, mainly at three-way junctions, and back to tubules. Plant reticulon family proteins (RTNLB) tubulate the ER by dimerization and oligomerization, creating localized ER membrane tensions that result in membrane curvature. Some RTNLB ER -shaping proteins are present in the plasmodesmata (PD ) proteome and may contribute to the formation of the desmotubule, the axial ER -derived structure that traverses primary PD . Here, we investigate the binding partners of two PD -resident reticulon proteins, RTNLB3 and RTNLB6, that are located in primary PD at cytokinesis in tobacco ( Nicotiana tabacum ). Coimmunoprecipitation of green fluorescent protein-tagged RTNLB3 and RTNLB6 followed by mass spectrometry detected a high percentage of known PD -localized proteins as well as plasma membrane proteins with putative membrane-anchoring roles. Förster resonance energy transfer by fluorescence lifetime imaging microscopy assays revealed a highly significant interaction of the detected PD proteins with the bait RTNLB proteins. Our data suggest that RTNLB proteins, in addition to a role in ER modeling, may play important roles in linking the cortical ER to the plasma membrane.